2010
DOI: 10.1080/17461391003699062
|View full text |Cite
|
Sign up to set email alerts
|

Match activities of top‐class female soccer assistant referees in relation to the offside line

Abstract: The aim of this study was to examine the match activities of top-class female assistant referees (mean age 34.8 years, s =3.5; stature 1.64 m, s=0.05; weight 58.1 kg, s=7.4; body mass index 21.6 kg • m~2, s=2.4) in relation to the offside line. Computerized match analyses were performed on 14 top-class assistant referees during 10 matches (a total of 20 observations) from the 2006 Federation Internationale de Football Association (FIFA) under-20 Women's World Championship held in Russia. In addition, the posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…ARs are encouraged to align with the offside line because this is considered the optimal position for judging offside (IFAB 2018 , Practical Guidelines for Match Officials, p.184). However, studies have revealed that ARs do not perfectly align themselves with the offside line in a match but are often standing ahead or behind the offside line (e.g., Mallo et al 2010 ; Oudejans et al 2005 ). When the AR is standing ahead, or behind the offside line, the probability of flag errors (false alarms) or non-flag errors (misses) might increase depending on the particular spatial configuration of the AR, the second-last defender, and the forward (see Oudejans et al 2005 , for a detailed description).…”
Section: Introductionmentioning
confidence: 99%
“…ARs are encouraged to align with the offside line because this is considered the optimal position for judging offside (IFAB 2018 , Practical Guidelines for Match Officials, p.184). However, studies have revealed that ARs do not perfectly align themselves with the offside line in a match but are often standing ahead or behind the offside line (e.g., Mallo et al 2010 ; Oudejans et al 2005 ). When the AR is standing ahead, or behind the offside line, the probability of flag errors (false alarms) or non-flag errors (misses) might increase depending on the particular spatial configuration of the AR, the second-last defender, and the forward (see Oudejans et al 2005 , for a detailed description).…”
Section: Introductionmentioning
confidence: 99%
“…4 So far, sport science has mainly focused on the kinematic and physical factors that determine refereeing decisions. [5][6][7][8][9][10][11][12] On the subject of perceptual cues, research has predominantly discussed the optical error versus the flash-lag hypothesis. [2][3][4]9,[13][14][15][16] Here Oudejans et al 9,16 showed an increasing number of incorrect offside decisions due to refereeing assistant's position relative to the offside line and the corresponding angle of view.…”
Section: Introductionmentioning
confidence: 99%
“…So far, sport science has mainly focused on the kinematic and physical factors that determine refereeing decisions . On the subject of perceptual cues, research has predominantly discussed the optical error versus the flash‐lag hypothesis .…”
Section: Introductionmentioning
confidence: 99%